Mesenchymal stromal cells mediated delivery of photoactive nanoparticles inhibits osteosarcoma growth in vitro and in a murine in vivo ectopic model - Stefania Lenna; Chiara Bellotti; Serena Duchi; Elisa Martella; Marta Columbaro; Barbara Dozza; Marco Ballestri; Andrea Guerrini; Giovanna Sotgiu; Tommaso Frisoni; Luca Cevolani; Greta Varchi; et al. (Journal of Experimental & Clinical Cancer Research, 2020)
Abstract Background Osteosarcoma (OS) is an aggressive malignant neoplasm that still suffers from poor prognosis in the case of distal metastases or occurrence of multi-drug resistance. It is therefore crucial to find novel therapeutic options able to go beyond these limitations and improve patients’ survival. The objective of this study is to exploit the intrinsic properties of mesenchymal stromal cells (MSCs) to migrate and infiltrate the tumor stroma to specifically deliver therapeutic agents directly to cancer cells. In particular, we aimed to test the efficacy of the photoactivation of MSCs loaded with nanoparticles in vitro and in a murine in vivo ectopic osteosarcoma model. Methods AlPcS4@FNPs were produced by adding tetra-sulfonated aluminum phthalocyanine (AlPcS4) to an aqueous solution of positively charged poly-methyl methacrylate core-shell fluorescent nanoparticles (FNPs). The photodynamic therapy (PDT) effect is achieved by activation of the photosensitizer AlPcS4 in the near-infrared light with an LED source. Human MSCs were isolated from the bone marrow of five donors to account for inter-patients variability and used in this study after being evaluated for their clonogenicity, multipotency and immunophenotypic profile. MSC lines were then tested for the ability to internalize and retain the nanoparticles, along with their migratory properties in vitro. Photoactivation effect was evaluated both in a monolayer (2D) co-culture of AlPcS4@FNPs loaded MSCs with human OS cells (SaOS-2) and in tridimensional (3D) multicellular spheroids (AlPcS4@FNPs loaded MSCs with human OS cells, MG-63). Cell death was assessed by AnnexinV/PI and Live&Dead CalceinAM/EthD staining in 2D, while in the 3D co-culture, the cell killing effect was measured through ATP content, CalceinAM/EthD staining and TEM imaging. We also evaluated the effectiveness of AlPcS4@FNPs loaded MSCs as delivery systems and the ability of the photodynamic treatment to kill cancer cells in a subcutaneous mouse model of OS by bioluminescence imaging (BLI) and histology. Results MSCs internalized AlPcS4@FNPs without losing or altering their motility and viability in vitro. Photoactivation of AlPcS4@FNPs loaded MSCs induced high level of OS cells death in the 2D co-culture. Similarly, in the 3D co-culture (MSCs:OS ratios 1:1 or 1:3), a substantial decrease of both MSCs and OS cells viability was observed. Notably, when increasing the MSCs:OS ratio to 1:7, photoactivation still caused more than 40% cells death. When tested in an in vivo ectopic OS model, AlPcS4@FNPs loaded MSCs were able to decrease OS growth by 68% after two cycles of photoactivation. Conclusions Our findings demonstrate that MSCs can deliver functional photosensitizer-decorated nanoparticles in vitro and in vivo and inhibit OS tumor growth. MSCs may be an effective platform for the targeted delivery of therapeutic nanodrugs in a clinical scenario, alone or in combination with other osteosarcoma treatment modalities.